Isolation, Percentage Yield Determination, Characterization, and Proximate Analysis of Cellulose from Bean Pods, Sandbox, and Wheat Offal - Badejo, Olayemi Aderanti; Ogunneye, Adeyemi Lawrence; Braimoh, Durojaiye Saidi; Ogunmade, Taiwo Oludare; Alaka, Michael Olusegun (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Cellulose is the most abundant, renewable, biodegradable and biomass substance in nature. It exhibits high flexibility, elasticity and bio-compatibility among its other properties. During pre-treatment in this study, the agricultural wastes from bean pod, wheat offal and sandbox were milled separately using an unbranded machine, sieved with a 250μm mesh to obtain fine-powdered materials which were then soaked inside water for 24 hours before boiling. Isolation by alkaline hydrolysis with sodium hydroxide was carried out inside a locally designed steel reaction vessel with a detachable electrically controlled mechanical stirrer at 90oc for 2½,hrs. The cellulose obtained was bleached with sodium hypochlorite, NaOCl2 to remove unbounded materials and then characterized using Fourier Transfer Infrared (FTIR) spectroscopy, to determine the functional groups present. Percentage yields of 47.4%, 36.3% and 34.6% were obtained for wheat offal, bean pod and sandbox respectively. The result obtained showed that obtaining cellulose from these agricultural wastes is economically viable and sustainable. The proximate analysis of the raw agricultural wastes and isolated cellulose was carried out according to the Association of Analytical Chemistry (AOAC) method, to determine the ash, moisture, lignin, hemicellulose, fat, crude fibre and protein values. The results showed a drastic reduction of ash, lignin and some other parameters in the isolated cellulose. This further revealed that the cellulose obtained was suitable for modification and wider applicability. Obtaining cellulose from agricultural wastes of bean pods, wheat offal and sandboxes for productive activities would reduce the volume of unwanted materials in our communities and eliminate or control the harmful effects of pollution in our environment.